A new species of tarantula of the genus Euathlus (Araneae: Theraphosidae) from Chile: distribution and possible threats to its conservation - Andrés Taucare-Ríos; Sergio Ocares-Plaza; Fernando Pérez-Miles (Gayana)
We describe and illustrate a new species of tarantula of the genus Euathlus Ausserer, 1875, Euathlus walteri sp. nov. This species represents the first record for the genus in Tarapacá region, being the northernmost limit of its known distribution in Chile. Known and potential distribution are provided. Precipitations and altitude are the most important variables for its distribution. In addition, the conservation status of the new species is discussed, and it is proposed as Endangered (EN) according to IUCN criteria.